Regenerative livestock or sustainable livestock? - Urdaneta, Fatima (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
Sustainability has been recognized as a fundamental principle of development so that humanity can survive on this planet. However, there are still difficulties in translating its philosophical principles into the ability to make concrete decisions for its consolidation. Three factors that determine growth on planet earth, directly related to agricultural systems, have been identified: agricultural production, management of natural resources, and pollution. Therefore, sustainable agriculture must consider them both for the management of plant and animal populations, since both modify the environment to adapt it to their requirements, thus regenerative practices arise to recover the ability of ecosystems to restore themselves. In that sense, it is intended in this review to elucidate how the concepts and principles exposed are translated into a regenerative or a sustainable livestock. To achieve sustainability, it is necessary and essential, an integral management of processes with a holistic vision of the system by farmers and technicians, leading human talents willing to learn different and new technologies, and motivated trained personnel in sustainable techniques that incorporate agroecological and regenerative practices, all on the basis of financial planning. Regenerative livestock per se as an emerging paradigm is very promising, but still requires local research. It is concluded that there is no single model of sustainable livestock, there are no recipes or technological packages, it is governed by the principles that aim at the balance of its dimensions (social, economic, environmental and institutional political governance).